IMPLEMENTASI SISTEM LABVIEW DALAM PENGUMPULAN DATA TEKANAN DAN ALIRAN DI FASILITAS PASCONEL - Yusuf, Nurdiyanto (Jurnal Ilmiah Multidisiplin, 2023)
The unsafe incidents in the Nuclear Reactors at the Chernobyl and Fukushima Dai-ichi Nuclear Power Plants were caused by disruptions to the internal reactor core elements, such as nuclear fuel and the electrical flow supplying the cooling systems. As a result, a complete cooling system failure (blackout) occurred, leading to a significant increase in the reactor core temperature and even the melting of the reactor core. A testing facility has been constructed to study the utilization of large-scale passive cooling systems. This facility is known as the Passive Condensation Experimental Loop (PASCONEL). PASCONEL facility is equipped with components like Pressure Transmitters on Heat Pipe 1, Pressure Transmitters on Heat Pipe 2, Pressure Transmitters on the Main Steam Generator, as well as Inlet and Outlet Flow Meters on the Main Steam Generator. In this research, the approach employed involves static testing of the facility for a duration of 24 hours. The objective of this testing is to gather data that can be used to analyze the performance of all installed components within the facility. The results of this data analysis will indicate whether all components function as intended.